Sobre educar na creche: é possível pensar em currículo para crianças de zero a três anos? - Amorim., Ana Luisa Nogueira de (2011)
This thesis aimed to understand whether and how national policies on early childhood education and curriculum were reinterpreted and transformed into policies and practices based on the analysis of the curriculum in action developed with children 0 to 3 years in public daycares in the city of Santa Rita/PB. Assume that there is a mismatch between the policies guiding the curriculum for early childhood education and what happens in the nursery rooms. Adopted as a conceptual framework for analyzing the broad understanding of curriculum and the possibility of him being taken in the segment from 0 to 3 years, given the specificity of early childhood education and understanding that young children are at the same time, dependent and potentially capable. Moreover, this work defends the concept of early childhood education as a right of children. So discuss the possibility of building this curriculum, emphasizing the need for institutions to develop their pedagogical/curricular activities linked in systematic and interrelated education and care. The qualitative study included three phases: analysis of national and local documents, observation of the moments of planning and observation made during the months from April to November 2010 in four nursery rooms municipal daycares. The dialectical method guided the study that sought to capture the whole, considering the interrelationships between policies (national and local) and curriculum practices, and content analysis guided the analysis of empirical data. In general, the results indicate mismatches exist between the documents national/local and the curriculum in action, revealing the distance between the curriculum proposal, planning monthly with the early childhood education teachers and the curriculum in action observed in the nursery classrooms, where predominated improvised and spontaneous actions. The analysis showed that local policies disregarded the local educational reality, which contributed to the proposal was not accepted by all, not implemented in practice. These mismatches reinforce the understanding of the denial of the right of the small child to a early childhood education of good quality and the need for public policies to be extended in the direction of expanding educational spaces for political and pedagogical construction inside the daycare so that they can develop locally and implement their pedagogical/curriculum. Another result points shows not to overcome the dichotomy care for and educate the daycare that was expressed in the allocation of professionals without the minimum qualification required for the educational work with children and in pedagogical practices/curriculum unsystematic, improvised found in nurseries. These actions ignore the inseparability of care and education and the ability of children as intelligent beings and cultural producers. Hence our assertion that the systematization of the curriculum for children 0-3 years old is not only possible, it is necessary to guarantee the educational rights of children to educational experiences that enable them to develop full and complete.